Do Not Miss the Tumor: A Novel Presentation of Osteosarcoma. (13th May 2021) - DePalma, Michael; Gupta, Sachin; Nguyen, Jie; Talwar, Divya; Arkader, Alexandre; Wells, Lawrence
Abstract : Antalgic gait is a common clinical presentation among pediatric patients and can have many different etiologies, with rare life-threatening etiologies including primary bone malignancies. Osteosarcoma is the most common primary malignancy of bone in pediatric and adolescent patients. The incidence rate of osteosarcoma has been reported as high as 5 to 7 per million among patients 19 years old or younger with males slightly more affected than females and African-Americans more than other racial groups. This report describes the case of a five-year-old African-American female who presented with an antalgic gait secondary to osteosarcoma in the left distal femur and follows her through treatment. In this case, the age is atypical as the peak incidence for osteosarcoma is around 16 years of age and is postulated to coincide with growth spurts. Osteosarcoma can have a range of presentations making it difficult to diagnose, which can cause delays in treatment and potential poor patient outcomes. Due to this, such a diagnosis must be included in the differential for patients presenting with antalgic gait. Because primary-care physicians and pediatricians may be the first medical providers to encounter patients with osteosarcoma, it is imperative that such clinicians are familiar with the signs and symptoms associated with osteosarcomas in order to reduce the risk of metastasis and disease progression and prevent treatment delays. Additionally, we believe these clinicians should have a low threshold to refer patients to orthopedists or oncologic specialists in the cases of persistent pain or inconsistencies with history, physical exam, and diagnostic studies. Finally, direct communication and discussion between radiologists and referring clinicians helps decrease delays in diagnosing of osteosarcoma and other life-threatening conditions.